Dissociative disorders in Turkish inpatients with conversion disorder - Tezcan, E; Atmaca, M; Kuloglu, M; Gecici, O; Buyukbayram, A; Tutkun, H (W B Saunders Co-Elsevier Inc, 2003)
The aim of our study was to determine the frequency of dissociative disorders (DDs) among inpatients with conversion disorder (CD) in a university clinic settled in Eastern Turkey. During a period of 24 months, 59 consecutively admitted adult CD patients were screened with the Dissociative Experience Scale (DES). Patients who scored above 30 (DDs group) did not differ by age or gender from a group of inpatients who scored below 10 on the scale (comparison group). All patients in the two groups were then interviewed in a blind manner using the Dissociative Disorders Interview Schedule (DDIS) and Structured Interview for DSM-IV Dissociative Disorders (SCID-D). According to the SCID-D, 18 of 59 patients (30.5%) received a diagnosis of dissociative disorder; nine of these 18 patients (50%) were diagnosed as having dissociative identity disorder, eight (44.4%) were diagnosed as having dissociative disorder not otherwise specified (NOS), and one (5.6%) was diagnosed as having dissociative amnesia. Accordingly to the DDIS, borderline personality disorder was frequent in the DDs group, and all of the patients in the DDs group reported sexual abuse and neglect during childhood, latency, or adolescence. A high proportion of CD patients have significant dissociative pathology. The proper diagnosis of these patients has important implications for their clinical course. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: Multiple Personality-Disorder; Structured Interview Data; Psychiatric-Inpatients; Identity Disorder; Childhood Abuse; Experiences; Frequency; Borderline; Pseudoseizures; Symptoms